The Effect of Pubertal Stage on the Concentrations of the Novel Adipomyokine, Irisin, in Male Adolescents - Demet Taş; Alkım Akman Öden; Sinem Akgül; Ziya E. Metin; Aslı Pınar; Nuray Kanbur (Galenos Yayincilik, 2020)
Objective:Irisin is a recently discovered protein and is defined as an adipomyokine. The relation of irisin with carbohydrate metabolism and other hormone parameters have been investigated. However, studies evaluating the relationship between irisin and puberty are limited and inconclusive. The aim was to evaluate serum concentrations of irisin during different pubertal stages in male adolescents.Methods:The study included normal weight pubertal male adolescents between the ages of 136/12-1411/12 who had entered puberty. Fasting serum irisin concentrations were evaluated, and bioelectrical impedance analysis was used to measure body fat ratio (BFR) and fat-free mass (FFM). BFR was also calculated by caliper measurement of subcutaneous fat at the triceps.Results:Sixty-eight adolescents were enrolled. The number of adolescents in pubertal stage 2, 3, 4 and 5 were n=17 (25%), n=13 (19.1%), n=21 (30.1%) and n=17 (25%), respectively. The median values of the irisin are 8.80, 8.20, 9.15 and 7.24 ng/mL according to the 2-5 pubertal stages, respectively. The levels of circulating irisin did not differ according to the pubertal stage. Additionally, there was no significant relationship between irisin levels and body fat percentage or FFM.Conclusion:Irisin levels do not differ after the onset of puberty or with progressing pubertal maturation. This study strengthens the evidence that there is no change in irisin concentration as puberty progresses. This may have important implications when using this adipomyokine in the future for diagnosis or treatment of obesity-related diseases.